A Retrospective Cohort Study Comparing the Safety and Efficacy of Minimally Invasive Versus Open Surgical Techniques in the Treatment of Spinal Metastases. Issue 8 (October 2017) - Hikata, Tomohiro; Isogai, Norihiro; Shiono, Yuta; Funao, Haruki; Okada, Eijiro; Fujita, Nobuyuki; Iwanami, Akio; Watanabe, Kota; Tsuji, Takashi; Nakamura, Masaya; Matsumoto, Morio; Ishii, Ken
Abstract : Study Design: A retrospective cohort study. Objective: This study was conducted to assess the invasiveness, efficacy, and safety of minimally invasive spine stabilization (MISt) for metastatic spinal tumor patients with short life expectancy. Summary of Background Data: Conventional open surgery for metastatic spinal tumors has the disadvantages of significant blood loss, potential infection, damage to back muscles, and extended hospital stays. The minimally invasive spine surgery has changed the treatment of metastatic spinal tumors radically and fundamentally. Materials and Methods: We retrospectively reviewed data from 50 consecutive patients registered with the Keio Spine Research Group (KSRG) who underwent posterior palliative surgery for metastatic spinal tumors from January 2009 to June 2015. Of these, 25 patients underwent MISt surgery (M group), and 25 underwent conventional open surgery (C group). The patients were assessed by demographic data, surgical invasiveness, complications, pain improvement, and neurological recovery. Results: The 2 groups did not differ significantly in baseline characteristics. The M group had significantly less blood loss (M, 340.1 mL; C, 714.3 mL; P =0.005), less postoperative drainage (M, 136.0 mL; C, 627.0 mL; P <0.001), lower rates of red blood cell transfusion (M, 3 cases; C, 10 cases; P =0.029), and a shorter postoperative period of bed rest (M, 2.0 d; C, 3.6 d; P <0.001), compared with the C group. The perioperative complication rates were significantly lower ( P =0.012) in the M group (3 patients, 12%) than in the C group (11 patients, 44%). Neurological deficits and pain improved significantly and comparably in the 2 groups after surgery. Conclusions: MISt is a less invasive and effective alternative surgery to conventional open surgery for metastatic spinal tumors. MISt should be considered as a valid option for the treatment of metastatic spinal tumor patients with a short life expectancy. Level of Evidence: Level 3.